2020
DOI: 10.3390/ijms21207782
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in the Left and Right Ventricle of the Late Phase of Post-Infarction Heart Failure

Abstract: While necroptosis has been shown to contribute to the pathogenesis of post-infarction heart failure (HF), the role of autophagy remains unclear. Likewise, linkage between these two cell death modalities has not been sufficiently investigated. HF was induced by 60-min left coronary occlusion in adult Wistar rats and heart function was assessed 6 weeks later followed by immunoblotting analysis of necroptotic and autophagic proteins in both the left (LV) and right ventricle (RV). HF had no effect on RIP1 and RIP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, a subsequent study reported that RIPK3 expression is primarily upregulated in the left ventricle of failing hearts 6 weeks after 60-min coronary occlusion, whereas RIPK3 expression is downregulated in right ventricle. On the other hand, MLKL expression is only elevated in the right ventricle and is unhanged in the left ventricle of failing heart 6 weeks after 60-min coronary occlusion [41]. The basis of these discrepancies is still unclear but indicate different responses and/or different signals regulating necroptotic cell death in left/right ventricles during myocardial ischemia.…”
Section: Cell Deathmentioning
confidence: 99%
“…Interestingly, a subsequent study reported that RIPK3 expression is primarily upregulated in the left ventricle of failing hearts 6 weeks after 60-min coronary occlusion, whereas RIPK3 expression is downregulated in right ventricle. On the other hand, MLKL expression is only elevated in the right ventricle and is unhanged in the left ventricle of failing heart 6 weeks after 60-min coronary occlusion [41]. The basis of these discrepancies is still unclear but indicate different responses and/or different signals regulating necroptotic cell death in left/right ventricles during myocardial ischemia.…”
Section: Cell Deathmentioning
confidence: 99%
“…However, due to improvements in laboratory techniques for accurate identification and measurement of apoptosis [ 17 , 18 ], the contribution of apoptosis to the extent of infarct size, as well as to the pathogenesis of ischemic heart disease and heart failure has been questioned. In fact, many studies dealing with acute or chronic ischemic heart damage have indicated only a minor role of apoptosis in such injury [ 10 , 19 , 20 , 21 , 22 ]. Likewise, the level of necrosis has been shown to be sevenfold 7-fold greater than apoptosis in patients with ischemic cardiomyopathy or idiopathic dilated cardiomyopathy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of MI and post-ischemic HF, these cell death programs produce deleterious cellular responses; however, it has not been clarified to which extent these contribute to the development of infarct size and what is the exact proportion of their occurrence in any particular cardiac disease. It has been suggested that in some cases, the number of cells dying due to these individual necrosis-like deaths (besides others such as autophagy-dependent cell death and parthanatos) may outnumber those due to apoptosis [ 10 , 19 , 20 , 33 , 34 ]. These pathways can be stand-alone cell death modalities, but can also co-exist independently or sequentially, suggesting that these modes of cellular death overlap and utilize common signaling components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors conclude that HeC may contribute to cardioprotection by increasing fibroblast migration, but not by releasing protective medium extracellular vesicles or soluble factors from cardiac fibroblasts. Lichý et al [ 9 ] in their study revealed the role of two types of cell death, necroptosis and autophagy, in the cardiac remodeling of the left and right ventricles in the late phase of post-infarction heart failure. While necroptosis is known to contribute to the pathogenesis of post-infarction heart failure, the role of autophagy remains unclear.…”
mentioning
confidence: 99%